Optimal Layer-based Unequal Error Protection for Robust JPEG 2000 Images and Video Transmission over Wireless Channels - AGUEH, max; soude, henoc (My University, 2009)
In this paper we propose an optimal layer-oriented Unequal Error Protection Forward Error Correction rate allocation scheme for efficient transmission of JPEG 2000 codestreams over wireless channels. The main advantages of the proposed scheme are its optimality, its compliance to Wireless JPEG 2000 (the 11th part of JPEG 2000 standard) and its low time consumption. We demonstrate that our proposed scheme outperforms the layer oriented FEC scheme proposed by Z. Guo et al and other existing layer based FEC schemes. We also show that, due to its low run time, our layer based scheme is a good candidate for highly time constrained motion JPEG 2000 video streaming applications, thus, in this sense, its overcomes the limitation of optimal packet oriented FEC rate allocation scheme. We then validate the effectiveness of our proposed layer oriented scheme with a Wireless Motion JPEG 2000 client/server application.
Keywords: layer-oriented forward error correction; unequal error protection; wireless jpeg 2000; video streaming